2012
DOI: 10.4250/jcu.2012.20.3.134
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Carotid Artery Stiffness with Heart Function in Hypertensive Patients

Abstract: BackgroundThe strength of each heart beat and the stiffness of large arteries contribute to blood pressure (BP). When the large arteries are stiff and their resistance greater, the afterload increases and this may change the function of the heart. However, the relation between common carotid artery stiffness and heart function in hypertensive patients has not been clarified.MethodsTwo hundred and twenty hypertensive patients underwent transthoracic and carotid echocardiography. Measurements of local arterial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
4
22
0
Order By: Relevance
“…In accordance with our study, a recent meta‐analysis reported that the prevalence of LV hypertrophy was about 3‐fold greater in patients with LA enlargement than those without . Additionally, investigators have shown that LA diameter is independently associated with arterial stiffness, which may affect the development of LV diastolic dysfunction. Furthermore, in patients with HFnEF, common comorbidities such as coronary artery disease, diabetes mellitus, obesity, and renal dysfunction may result in volume overload and myocardial injury of atrium .…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with our study, a recent meta‐analysis reported that the prevalence of LV hypertrophy was about 3‐fold greater in patients with LA enlargement than those without . Additionally, investigators have shown that LA diameter is independently associated with arterial stiffness, which may affect the development of LV diastolic dysfunction. Furthermore, in patients with HFnEF, common comorbidities such as coronary artery disease, diabetes mellitus, obesity, and renal dysfunction may result in volume overload and myocardial injury of atrium .…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies attempted to report the relationship between atherosclerotic CVD and arterial strain. Indeed, several studies documented that the changes in elastic properties due to aging or cardiovascular RFs could be successfully evaluated with carotid strain values that were acquired using the speckle tracking method . In addition, another recent study showed that circumferential strain and strain rate were significantly correlated with a previous stroke event .…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, several studies documented that the changes in elastic properties due to aging or cardiovascular RFs could be successfully evaluated with carotid strain values that were acquired using the speckle tracking method. 6,7,13 In addition, another recent study showed that circumferential strain and strain rate were significantly correlated with a previous stroke event. 14 Our present study's findings expand on these data by demonstrating the feasibility of assessing circumferential and radial movements of the CCA in both transverse and longitudinal carotid B-mode ultrasonograms to determine the relationship to atherothrombotic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Measures of the CCA stiffness have been associated with risk of ischemic stroke and dementia but not of coronary artery disease [14,15,16,17,18]. However, with advancing age, disproportionately increased proximal aortic stiffness may match the stiffness of CCA [14], reduce the impedance mismatch, and tighten the link between CCA stiffness and LV structure and function [9,19]. In this context, measures of the CCA stiffness may become a surrogate for ascending aortic stiffness and provide additional information on the pathogenesis of heart failure beyond cf-PWV, an index of arterial aging [9,20].…”
Section: Introductionmentioning
confidence: 99%